1986
DOI: 10.1002/bin.2360010106
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of contingent restraint on aggression, self‐injury, and property destruction of institutionalized mentally retarded persons

Abstract: This study was a retrospective evaluation of in place treatment procedures. Clinical data were reviewed from 45 cases in which contingent restraint was employed in an effort to modify the inappropriate behaviors of institutionalized mentally retarded persons. Statistically significant decrements in the rates of inappropriate behavior were detected over the 18 months of study. Clinically meaningful improvement in the rates of behavior were detected in 53% of the cases in which the target behavior was either agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Restraint has been employed for many years in a variety of hospital and residential facilities as an intervention for people with mental disorders and intellectual disabilities to stop violent episodes or physical aggression toward self or others (Spreat & Stepansky 1986; Fisher 1994; Harris 1996). In facilities serving persons with intellectual disabilities, restraint has been used not just as an emergency or crisis‐intervention procedure to prevent injuries to self or others but has also been used as a component of behaviour intervention plans with many studies documenting its effectiveness along with other interventions in reducing target behaviours (Luiselli 1992; Van Houten et al.…”
Section: Introductionmentioning
confidence: 99%
“…Restraint has been employed for many years in a variety of hospital and residential facilities as an intervention for people with mental disorders and intellectual disabilities to stop violent episodes or physical aggression toward self or others (Spreat & Stepansky 1986; Fisher 1994; Harris 1996). In facilities serving persons with intellectual disabilities, restraint has been used not just as an emergency or crisis‐intervention procedure to prevent injuries to self or others but has also been used as a component of behaviour intervention plans with many studies documenting its effectiveness along with other interventions in reducing target behaviours (Luiselli 1992; Van Houten et al.…”
Section: Introductionmentioning
confidence: 99%
“…The commonest form of direct mechanical restraint in use is the restraining chair and/or belts for those who are mobile (Harris, 1996). Restraint can either last for a few minutes for the purpose of any haematological/physical investigations, or for longer, either in hospital or residential settings to prevent physical harm towards self or others (Spreat and Stepansky, 1986;Fisher et al, 1997;Emerson, 2002). In a series of studies conducted between 1994 and 2000, Emerson (2002) showed that 5 percent of children with intellectual disabilities who self injured were ''usually'' or ''sometimes'' managed by physical restraint.…”
Section: Physical Restraintmentioning
confidence: 99%